Evaluation of 3D-Printed titanium alloy using eddy current testing with high-sensitivity magnetic sensor. (March 2019) - He, Dongfeng; Wang, Zhi; Kusano, Masahiro; Kishimoto, Satoshi; Watanabe, Makoto
Abstract: We developed ECT systems using high-sensitivity magnetic sensors with small size; and used the systems to evaluate a titanium alloy sample prepared by a 3D laser printer. Two systems were used. In the first system, a small excitation coil was wrapped around the amorphous wire, and the excitation frequency was chosen to be 100 kHz. In the second system, a large circular coil was used to surround the test sample, and the excitation frequency was chosen to be 70 kHz. The image of the scanning result shows that both ECT excitation methods were able to detect the positions of flaws in the test sample. Moreover, the sizes of the flaws could be seen in the phase image result of the first ECT excitation method, and the interaction between the eddy current and the flaws could be observed in the amplitude imaging result of the second ECT excitation method. We also compared the results with that of traditional inductive coil ECT system.